2014
DOI: 10.1016/j.aju.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic abscess: Objective assessment of the treatment approach in the absence of guidelines

Abstract: ObjectiveTo assess the outcome of the drainage procedure used for treating a prostatic abscess, and to propose a treatment algorithm to reduce the morbidity and the need for re-treatment.Patients and methodsWe retrospectively reviewed patients who were admitted and received an interventional treatment for a prostatic abscess. All baseline relevant variables were reviewed. Details of the intervention, laboratory data, duration of hospital stay, follow-up data and re-admissions were recorded.ResultsA prostatic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…These patients, who are frequently older with coincident outlet obstruction, are at risk for PA from direct introduction of bacteria into the prostate. Along with multiple case reports, previous cross‐sectional studies have shown that 8–11% of patients presenting with PA had recently undergone prostate biopsies . In two such cases, PA was the result of infection with multidrug‐resistant Escherichia coli .…”
Section: Etiology and Natural Historymentioning
confidence: 91%
See 3 more Smart Citations
“…These patients, who are frequently older with coincident outlet obstruction, are at risk for PA from direct introduction of bacteria into the prostate. Along with multiple case reports, previous cross‐sectional studies have shown that 8–11% of patients presenting with PA had recently undergone prostate biopsies . In two such cases, PA was the result of infection with multidrug‐resistant Escherichia coli .…”
Section: Etiology and Natural Historymentioning
confidence: 91%
“…Drainage can be carried out transperineally, but no evidence supports this technique as superior in fact, reports have detailed the development of periurethral or perineal abscesses after perineal aspiration requiring open incision and drainage . As most urologists are comfortable with the transrectal approach, we recommend this as the standard for ultrasound‐guided drainage . Of the multiple advantages to this technique, foremost is the ability to carry out aspiration at the bedside with local anesthesia.…”
Section: Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…In the series of LIM JW et al [17], transrectal ultrasound drainage resulted in 86% success, out of only 14 treated patients, two necessitated another therapeutic modality, namely perineal incision drainage in one Case and trans-urethral resection in the second case. ELSHAL AM et al [18] propose an algorithm for the management of prostatic abscess (Figure 3) based on the age of the patient, the size of the prostate and the associated urinary disorders.…”
Section: This Is An Open Access Article Distributed Under the Creativmentioning
confidence: 99%